CORRELATION OF REGRESSION ON EMPLOYEE PERFORMANCE: IN-DEPTH ANALYSIS OF THE RELATIONSHIP BETWEEN COMPETENCY AND COMPENSATION AT THE HUMAN CAPITAL MANAGEMENT SERVICE OF PT XYZ - Maulidin, Wildan Fatchan; Debora, Fransisca (Politeknik META Industri Cikarang, 2024)
Employee performance management is crucial for achieving organizational goals, especially in dynamic industries like aviation. PT XYZ, a leading aircraft maintenance provider, recognizes the importance of optimizing employee performance. Individual competency and organizational compensation are key factors influencing this performance. Certification, as proof of competency, ensures employees possess the necessary skills, yet it is becoming rare in Human Resource Management services, potentially hampering performance. In addition, PT XYZ survey data highlights compensation as a weak point, impacting overall employee performance. This research aims to examine the relationship between competency, compensation, and employee performance at PT XYZ's Human Capital Management Service using the correlation regression method. The findings indicate that both competency and compensation significantly influence employee performance, with a correlation value of 0.696 (69.6%), indicating a strong relationship. Additionally, the analysis shows that competence and compensation together account for 48.4% of the variance in employee performance, while the remaining 51.6% is influenced by other factors not examined in this research. Employee competency has a positive and significant influence on performance, with a regression coefficient value of 1.027, indicating that an increase in employee competency is directly proportional to an increase in their performance. In contrast, compensation shows no partial significant influence on performance, with a regression coefficient value of -0.092. The study recommends that PT XYZ’s Human Capital Management Department prioritize enhancing employee competency and reviewing compensation strategies to improve overall performance. This research contributes significantly to developing more effective human resource management policies in a competitive business environment.